Sharia Fintech Education for Disaster-Affected Communities in Palu City - Sofyan, Syaakir; Syamsu, Nur; Noval, Noval (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Datokarama Palu, 2023)
Amidst the rampant development of conventional fintech technology, Islamic fintech has emerged as an innovation combining Islamic finance principles with technological advancements. Islamic fintech is a financial solution that enables Muslims to conduct their daily economic activities following Sharia law, which prohibits usury (interest) and transactions that are not in line with principles of justice. This initiative is carried out to increase public interest in using Islamic fintech by educating communities affected by disasters in Huntap Duyu. The process involves stages of preparation, observation, discussion for activity determination, activity implementation, and evaluation. The activity results show positive outcomes in enhancing the community's understanding of Islamic fintech.